Assessment of Variability for Floral Characteristics and Out-Crossing Rate in CMS Lines of Hybrid Rice - Hasan, MJ; Kulsum, MU; Paul, AK; Biswas, PL; Rahman, MH; Ansari, A; Akter, A; Lipi, LF; Mohiuddin, SJ; Rafiq, M Zahid Al (Bangladesh Rice Journal, 2019)
The present investigation was aimed to clarify the interrelationship among various floral traits and out crossing rates. High mean value, range of variability and genotypic variance were observed for all the traits except anther length and breadth, stigma length and breadth. Close differences between genotypic and phenotypic variances and genotypic and phenotypic coefficient of variations were observed for all the traits. Considering all genetic parameters, selection based on panicle exertion rate, angle of florate opening, duration of florate opening, anther length, stigma exertion rate and out crossing rate seemed to be effective for the improvement of CMS lines. Out crossing rate had significant positive correlation with panicle exertion rate, angle of florate opening, duration of florate opening, filament length, stigma length, breadth and exertion rate exhibited interesting results, indicating selection with these traits might be possible without compromising seed yield loss. On the basis of direct selection through panicle exertion rate, angle and duration of florate opening, filament length and stigma exertion rate would significantly improve seed yield of CMS lines. Based on mean, range, genetic parameters, correlation coefficient and path coefficient values, direct selection of eight CMS lines IR79156A, BRRI7A, IR75608A, BRRI13A, BRRI35A, BRRI48A, BRRI50A and BRRI53A might be fruitful as good floral characteristics with high out crossing rate of CMS lines. Bangladesh Rice j. 2018, 22(2): 31-39